(untitled) (Research, Society and Development, 2020)
The objectives of this study were to analyze whether teachers are working with practical classes using scientific experiments in science teaching, to list the reasons why science classes in elementary school have few experiments and to propose improvements for a better effectiveness of classes, taking into account view the benefits of practical classes in teaching learning. To achieve the objectives, a quantitative methodology was used through a questionnaire for data collection at a school in the Municipality of Grajaú-MA, 148 students from the 8th and 9th grade answered the questionnaire. The results obtained are displayed in the form of graphs, in which it was possible to notice that students like classes with experiments, however the school has no structure so that students can practice this type of class more often. It is concluded that the practical classes with scientific experiments have been applied even if little and that this index of classes can increase a lot, being necessary measures for this to circumvent or alleviate the problem of not having adequate structure and equipment in the school for classes with experiments . One way to improve the current situation is the partnership between the school that was the object of study and higher institutions that can help with equipment or technical visits.